Dampak Konten Viral di Platform Instagram: Tantangan dan Konsekuensi - Allo, Karmila Pare; Widiawati, Wilda; Danindra, Fuad; Haliq, Muh. Idham; Harianto (Literatify: Trends in Library Developments, 2025)
The phenomenon of brainrot, or intellectual decline due to excessive information consumption, has become a serious issue in the digital era. Brainrot affects information literacy, knowledge management, and decision-making. This study employs a qualitative method with non-participatory observation to avoid bias. Data is obtained from social media through observations and screenshots of behaviors, expressions, and interaction patterns in reels, photos, and comments. The instruments used include internet networks, devices, and social media accounts. The research findings indicate that brainrot is triggered by an information tsunami, social media algorithms that prioritize viral content, and low information filtering capabilities. Its impacts include decreased focus, critical thinking, and knowledge management effectiveness at both individual and institutional levels. To address this issue, more adaptive information literacy, better digital time management, and the utilization of artificial intelligence-based technology to filter relevant information are necessary. This study aims to provide a deeper understanding of the process and effects of brainrot, as well as strategies to overcome it. Structured social media literacy improvement is an essential step in facing digital era challenges and enhancing productivity.